Occurrences of Regional Strong Es Irregularities and Corresponding Scintillations Characterized Using a High‐Temporal‐Resolution GNSS Network. Issue 11 (15th November 2021) - Sun, Wenjie; Hu, Lianhuan; Yang, Yuyan; Zhao, Xiukuan; Yang, Sipeng; Xie, Haiyong; Li, Yi; Liu, Libo; Ning, Baiqi; Li, Guozhu
Abstract: Strong sporadic E ( E s ) irregularities over China are investigated based on high‐temporal‐resolution total electron content (TEC) derived from two crossed chains of Beidou geostationary satellite (BD‐GEO) TEC receivers along 110°E and 23°N, respectively. The high resolution rate of TEC index (HR‐ROTI) calculated at an interval of 30 s, is proposed to characterize small‐scale strong E s irregularity structures. Based on the HR‐ROTI measurements and the typical drift velocity of E s 60 m/s, the scale sizes of strong E s irregularity structures were revealed to be mainly ∼7 km. The structures were mostly quasi‐periodically separated with distances of 7–16 km. Through a further statistical analysis of strong E s irregularity structures along the two chains, it was found that the E s irregularity structures predominantly occur during local summer at middle and low latitudes, with the occurrence rate peaking at ∼30°N. On average approximately 2–5 small‐scale strong E s irregularity structures may be embedded in one larger‐scale structure. Unlike the equatorial and low‐latitude F‐region irregularities which cause scintillations under most conditions, the strong E s irregularity characterized by HR‐ROTI caused scintillation with relatively low occurrence rates of 37% and 12% at middle and low latitudes, respectively. Plain Language Summary: The ionospheric sporadic E ( E s ) layer and associated irregularities were traditionally investigated and characterized based on observations from ground‐based radars, for example, ionosondes and very high frequency radars, which usually suffer from a small spatial distribution. Ever since strong E s were revealed to be detectable by ionospheric total electron content (TEC) measurements from ground‐based Global Navigation Satellite Systems (GNSS) receivers, the morphology of large‐scale strong E s structures has been studied over different regions. However, the occurrences of strong E s irregularity structures, with scale sizes down to a few kilometers along the same latitude/longitude are not clear. Whereas GNSS observations in a dense network provide a valuable dataset for E s investigation, the most commonly used measurements such as the L‐band amplitude scintillation index and the well‐defined rate of TEC index (ROTI) are for F‐region irregularities. No index specialized in identifying strong E s irregularities has been proposed. In this regard, the high resolution ROTI (HR‐ROTI) calculated at 30‐s interval is proposed to characterize E s irregularity structures with scale sizes down to a few kilometers. Based on the HR‐ROTI measured along two crossed GNSS receiver chains, the occurrences of strong E s irregularities along a specific longitude/latitude over China are investigated, which exhibited distinct features over different latitude regions. Key Points: High Resolution Rate‐Of‐TEC Index (HR‐ROTI) is introduced to characterize strong E s irregularity structures with scale sizes down to a few kilometers Strong E s over China tends to occur more frequently around 30°N, and be embedded with approximately 2–5 small‐scale structures in one larger structure The occurrence rates of amplitude scintillations under strong E s (with HR‐ROTI > 0.1 TECU/min) at middle and low latitudes are 37% and 12%, respectively